A new cross-protection dual-WDM-PON architecture with carrier-reuse colorless ONUs - Zhong, Wende (2013)
This paper proposes a new cross-protection colorless dual-WDM-PON architecture. The proposed protection scheme can provide 1 + 1 downstream protection and 1:1 upstream protection against both feeder fiber and distribution fiber failures by using the fiber links and AWGs of the neighboring WDM-PON. Wavelength is reused for the down- and up-stream transmissions in dual-WDM-PONs where gain-saturated reflective semi-conductor optical amplifiers (RSOAs) are employed as colorless transmitters in ONUs. The number of extra protection fibers is minimized and wavelength is much more efficiently utilized compared with other protection schemes. The feasibility and operation of the proposed dual-WDM-PON architecture are experimentally verified with 1.25 Gb/s for upstream and 2.5 Gb/s for downstream over 20 km single mode fiber transmission in both working and protection modes.